(untitled) (Altre Modernità, 2022)
The Coronavirus pandemic has upset not only the Italian school, revealing its unpreparedness on a technological level, but also students’ lives, altering their habits radically. Nevertheless, the young people of Generation Z have not been caught so unprepared by digital innovations: since a long time, in fact, by using the elementary structures of audiovisual language, they have been experimenting subjective screen experiences, which then become objects of new self-writing practices, considered more effective than traditional and multimedia writing. With Distance Learning (and the transformation of the school-building into a mediascape), these practices have expanded to the school environment: thus, students and teachers have found themselves acting together in the same single large media environment generated by the relocation of the school-device and the home-environment, with a short circuit between them. Their experiences have been witnessed by social media, a medial area in which both students and teachers, as mediantrophists, can adequately substantiate their digital emotions. In order to grasp the links between Distance Learning, screens, experiences and practices, we will analyze a textual corpus of the Italian area extracted from TikTok, an audiovisual social medium widely used by very young people, offering specific focuses on cases of teachers and students who have distinguished themselves in the media flow, quickly impressing themselves in the pandemic imagery of young Italians.